Tissue Distribution of Tolterodine, a Muscarinic Receptor Antagonist, and Transfer into Fetus and Milk in Mice - Påhlman, Ingrid; Ád’rgy, Roland; Nilvebrant, Lisbeth (Arzneimittelforschung, 2001)
Tolterodine ((R)-N,N-diisopropyl- 3- (2- hydroxy- 5 -methylphenyl)-3- phenylpropanamine, CAS 124937-51-5) is an anti -muscarinic agent developed specifically for the treatment of the overactive bladder. In this study, the extent and profile of tissue distribution of 14C- tolterodine, after single and repeat oral dosing, was investigated in the mouse. Overall, distribution of radioactivity in tissues was rapid, and there were no gender -specific differences. The concentration of radio activity in most tissues was similar to, or exceeded, that in blood. Highest concentrations were measured in gall bladder, urinary bladder, liver, kidneys and lungs, while the lowest concentration (10- times lower than in plasma) was seen in the brain. The distribution pattern after repeat oral dosing was similar to that after a single dose, although the decline in tissue concentrations was slower. Studies in pregnant mice showed that the distribution of radioactivity differed between dams and fetuses. Radioactivity was low and showed homogeneous distribution in the fetus, while a heterogeneous pat tern was seen in the dam. Highest concentrations were seen in the fetal liver, brain and spinal cord. Some accumulation was observed in the choroidplexus. Placental concentrations of radioactivity were generally higher than those in the fetus, with some accumulation in the yolk sac. Studies in suckling mouse pups showed low levels of exposure to drug -related radioactivity (around 0.2 % of the dose); the milk:plasma concentration ratio was 0.0-0.7. In conclusion, tolterodine and its metabolites are rapidly distributed into tissues following oral administration of radiolabeled drug in the mouse, with many tissues (including the fetus) reaching similar concentrations to that observed in blood. In other tissues, especially the eliminating organs, radio -activity levels were much higher than in blood. Penetration of the central nervous system was low, suggesting that the risk of deleterious effects on cognitive function may be lower with tolterodine than with more lipophilic antimuscarinic drugs.
Keywords: CAS 124937-51-5; Muscarinic receptor antagonist; Tolterodine, mouse, placental transfer, tissue distribution